Foreword to the special section - Dziubalska-Kołaczyk, Katarzyna; Wojtkowiak, Ewelina (Yearbook of the Poznan Linguistic Meeting, 2021)
This is the foreword to the special section with articles from the PLM2019 session titled “Modern phonetics and phonological representation: a new outlook on an old controversy”.